Where do ideas go? A spatial analysis of the patenting impact of publicly funded basic science - Toschi, Laura; Munari, Federico; Sobrero, Maurizio; Righi, Hérica Morais; Leonelli, Sebastiano (Research Policy, 2026)
As societal challenges loom larger, discoveries are in greater demand, and evaluating the impact of publicly funded programs attracts increasing attention. We contribute to this debate by focusing on the spatial influence of scientific discoveries funded through grants targeting frontier research. Our dataset includes information on 6671 EU ERC-funded projects between 2007 and 2016, 172,683 scientific publications generated by these grants, and 34,513 patents citing such publications. Building on linkages between scientific papers and patents via non-patent literature citations, we use the project as the unit of analysis and employ a two-stage regression model to examine the probability that ERC-funded publications are cited by patents and how these citations diffuse across space and time. The analyses on our final sample of 4977 ERC-funded projects, generating 151,574 publications that are cited by 34,007 patents confirmed our hypothesis that higher quality research leads to a broader and faster geographical diffusion and partially confirm the hypotheses that diffusion paths and speed differ by applicants, although these differences do not always show the same patters. Moreover, we also find that c) projects generating scientific output (publications) and technological outputs (patents) diffuse more broadly and faster; and d) projects led by more mobile and scientifically productive scientists diffuse more broadly and faster; We discuss these findings and show how they enhance and extend our understanding of the impact of science and its implications for policymakers and innovation scholars.